2012
DOI: 10.1167/iovs.11-9103
|View full text |Cite
|
Sign up to set email alerts
|

PTX3 Controls Activation of Matrix Metalloproteinase 1 and Apoptosis in Conjunctivochalasis Fibroblasts

Abstract: PURPOSE. Conjunctivochalasis (CCh) is an age-related inflammatory ocular surface disease manifesting redundant, loose conjunctiva folds. The pathogenic role of Pentraxin 3 (PTX3) in controlling upregulation of matrix metalloproteinase 1 (MMP-1) and MMP-3 in CCh remains undefined.METHODS. Cytolocation of PTX3 and apoptosis were compared by immunostaining and terminal deoxyribonucleotidyl transferase-mediated FITC-linked dUTP nick-end DNA labeling (TUNEL) assay between normal and CCh specimens containing the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Pentraxin‐3 is well known to reflect vascular inflammation derived from mainly ECs followed by VSMCs and macrophages and also is associated with apoptosis and plaque vulnerability . In the present study, increased pentraxin‐3 expression and increased activities of MMP‐2 and MMP‐9 as well as apoptosis induction in VSMCs by KP‐10 may be associated with atherosclerotic plaque instability.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Pentraxin‐3 is well known to reflect vascular inflammation derived from mainly ECs followed by VSMCs and macrophages and also is associated with apoptosis and plaque vulnerability . In the present study, increased pentraxin‐3 expression and increased activities of MMP‐2 and MMP‐9 as well as apoptosis induction in VSMCs by KP‐10 may be associated with atherosclerotic plaque instability.…”
Section: Discussionsupporting
confidence: 51%
“…Pentraxin-3 is well known to reflect vascular inflammation derived from mainly ECs followed by VSMCs and macrophages and also is associated with apoptosis and plaque vulnerability. [33][34][35][36] In the present study, increased pentraxin-3 expression and increased activities of MMP-2 and MMP-9 as well as apoptosis induction in VSMCs by KP-10 may be associated with atherosclerotic plaque instability. Previous reports showed that KPs downregulated MMP-2 and MMP-9 at both the transcriptional and protein levels in human renal carcinoma KU19-20 cells and fibrosarcoma HT-1080 cells, respectively.…”
Section: Discussionmentioning
confidence: 48%
“…They stated that pentraxin 3 expression might partake in apoptosis and pathogenesis of CCh by upregulating expression of matrix metalloproteinase-1 (MMP-1) and matrix metalloproteinase-3 (MMP-3). In another study of Guo et al19 the authors demonstrated that dysfunction of tumor necrosis factor-stimulated gene-6 might play a role in the pathogenesis of CCh by counteracting the transcription of MMP-1 and MMP-3 and the activation of MMP-1.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have demonstrated that PTX3 is involved in the removal of apoptotic cells during immune response [101112]. PTX3 siRNA knockdown was also shown to promoted cell death, characterized as apoptosis and necrosis, in the presence of proinflammatory cytokines such as IL-1β and TNF-α in conjunctivochalasis fibroblasts [13]. …”
mentioning
confidence: 99%